(untitled) (Innovaciones Educativas, 2021)
This article deals with the experience of students in teacher training with the creation of an animated Powtoon® video as audiovisual material for the development of their classes. The learning experience aims to design didactic proposals based on the creation of digital materials and is carried out with a number of students in teacher training, in a course at the School of Education Administration, with the support of the Technology Program Educational for Learning (PROTEA) of the School of Education of the University of Costa Rica. The methodology developed is based on a qualitative approach through the workshop technique. This is because it encourages knowing the perception of the student body regarding the creative process of a resource that supports the educational process. It is emphasized that the creation of the resources promotes a learning experience by virtue of the specific objectives. After the experience, the main finding has been that when the teaching person produces the DDM, elements are incorporated which properly contextualize their content towards the needs of the teaching process. Consequently, creative abilities are developed, knowledge apprehension is obtained and the results of the student’s learning process are optimized.